The performance of IHEP-NDL LGAD sensors after neutron irradiation. (20th August 2021) - Li, M.; Fan, Y.; Liu, B.; Cui, H.; Jia, X.; Li, S.; Yu, C.; Yang, X.; Wang, W.; Zhai, M.; Yang, T.; Wu, K.; et al.
Abstract: The performances of Low Gain Avalanche Diode (LGAD) sensors from a neutron irradiation campaign with fluences of 0.8 × 10 15, 1.5 × 10 15 and 2.5 × 10 15 n eq /cm 2 are reported in this article. These LGAD sensors are developed by the Institute of High Energy Physics, Chinese Academy of Sciences and the Novel Device Laboratory for the High Granularity Timing Detector of the High Luminosity Large Hadron Collider. The timing resolution and collected charge of the LGAD sensors were measured with electrons from a beta source. After irradiation with a fluence of 2.5 × 10 15 n eq /cm 2, the collected charge decreases from 40 fC to 7 fC, the signal-to-noise ratio deteriorates from 48 to 12, and the timing resolution increases from 29 ps to 39 ps.